2015
DOI: 10.5539/ass.v11n17p74
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Method Section in Engineering Research Articles

Abstract: Genre analysis is one of the common ways to analyse the rhetorical structure of a text. Previously, there are many genre analysis and rhetorical organisation studies on research articles (RAs) from different disciplines. Some of them focused on the whole RAs and some of them focused on certain sections of the RAs. This study attempts to identify the moves in the Method section of the Engineering RAs, and the most frequent verbs in the moves. The present study adopts a corpus-based analysis; 60 RAs from an Engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…Noorli (2011, as cited in Musa et al, 2015) argued that lexis is the basis of a language. Lewis (1993, as cited in Musa et al, 2015) asserted that a construction of meaning is identified from fixed words than from fixed structures. Musa and colleagues then claimed that grammatical expressions and the rhetorical structure of a text are closely linked with each other.…”
Section: Analysis Of Verb Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Noorli (2011, as cited in Musa et al, 2015) argued that lexis is the basis of a language. Lewis (1993, as cited in Musa et al, 2015) asserted that a construction of meaning is identified from fixed words than from fixed structures. Musa and colleagues then claimed that grammatical expressions and the rhetorical structure of a text are closely linked with each other.…”
Section: Analysis Of Verb Choicesmentioning
confidence: 99%
“…One interest of the present study is to look into the verb choices in every move which has been neglected by scholars. This linguistic category was already explored in the RA genre; however, it was identified in the methodology section of an RA conducted by Musa et al (2015). Investigating verbs in the RA abstract could provide a more illustrative representation of an RA as a whole discourse since abstract, containing the different sections of an RA, is generally conceived as the summary or condensed format of an RA.…”
Section: Introductionmentioning
confidence: 99%
“…Following this work of Swales (1990), a few noble research have been carried out in various parts of the RA. For instance, Abstract (e.g., Hyland & Tse, 2005), Introduction (e.g., Paltridge, 1994;Samraj, 2002;Samraj, 2005), Methods (e.g., Lim, 2006;Peacock, 2011;Musa et al, 2015), Results (e.g., Brett, 1994;Williams, 1999;Yang & Allison, 2003), and Discussion (e.g., Holmes, 1997;Holmes, 2001;Peacock, 2002). Numerous research has focused on the other conventional features of academic written discourse as well, such as the use of indirectness markers (Hinkel, 1997), tenses and passive voice (Hinkel, 2004), and the use of personal pronouns (Doncheva-Navrátilová, 2013).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Este trabajo está claramente basado en propuestas ya clásicas como la del modelo CARS (Create a Research Space) bajo el marco metodológico del Genre Analysis (Swales, 1990). De manera más específica, los investigadores se han enfocado en analizar secciones del AIC, tales como las de introducción (Samraj, 2002;Swales, 2004) o la de método (Kallet, 2004;Musa, Khamis y Zanariah, 2015). Esta atención hacia la escritura académica ha derivado también en la investigación del resumen.…”
Section: Géneros Discursivosunclassified
“…El corpus de la presente investigación está compuesto por un total de 60 resúmenes extraídos de AIC publicados en seis revistas científicas de lingüística, tres correspondientes a cada lengua. Este número es similar al recopilado en otras investigaciones de naturaleza semejante (Diani, 2014;Ibáñez et al, 2015;Lorés-Sanz, 2004;Musa et al, 2015;Pho, 2008). Las revistas seleccionadas para la creación del corpus están indexadas en múltiples bases de datos reconocidas, tales como SciELO y SCOPUS.…”
Section: Metodología Corpusunclassified